32 Premature vascular ageing in hypertension: role of aldosterone and nadph oxidases. (17th November 2015) - Harvey, AP; Montezano, AC; Hood, KY; Lopes, RAM; Ceravolo, GS; Yabe-Nishimura, C; Graham, D; Touyz, RM
Abstract : In hypertension, the vasculature undergoes premature ageing. The role of aldosterone and NADPH oxidases (Nox's) in the molecular mechanisms of age-associated vascular damage is unclear. We hypothesise that premature ageing in hypertension is due to increased aldosterone-induced Nox activation. We assessed vascular ageing in resistance arteries and vascular smooth muscle cells (VSMCs) from adult WKY (18 weeks), aged WKY (52 weeks) and adult stroke-prone spontaneously hypertensive (SHRSP) rats. Blood pressure (BP) was measured by tail-cuff. Vascular structure and function were analysed by pressure and wire myography. Gene and protein expression were assessed by qPCR and immunoblotting. We observed elevated BP, endothelial dysfunction and hypercontractility in vessels from SHRSP (vs. WKY). Vascular contraction in aged WKY rats was similar to SHRSP rats. Increased stiffness was observed in mesenteric arteries from aged WKY and SHRSP rats (vs. WKY). Nox2, NoxA1 and NoxO1 mRNA expression was increased (p < 0.05; vs. WKY). Nox1 mRNA expression was increased in SHRSP rats (p < 0.05; vs. WKY). Levels of MCP-1 and RANTES, ageing-related inflammatory markers, and cell cycle inhibitors, p21 and p27, were increased in aged WKY and SHRSP rats (p < 0.05; vs. WKY). H2AX (ageing-associated DNA damage marker– 1.5-fold) and aldosterone (6-fold) levels were increased in SHRSP rats (p < 0.05; vs. WKY). Aldosterone-induced Nox1 mRNA expression was exacerbated in SHRSP VSMC's. p66SHC activation by aldosterone was blocked by ML171 (Nox1 inhibitor) in WKY and SHRSP VSMCs, and blunted in the vasculature from Nox1 knockout mice. In conclusion, Nox1 seems to play a crucial role in aldosterone-induced premature ageing in hypertension.